Elite interviewing in media and communications policy research. (1st March 2015) - Herzog, Christian; Ali, Christopher
This article critically examines the use of elite interviews in media and communications policy research. It addresses the fit between various analytical frameworks and elite interviews as a primary source of data, interviewee selection, access, the conduct of interviews and data analysis. It is argued that there is a lack of methodological explanation and reflection in our field of study. Partly, this is determined by the preferences of publishers and space constrains but also a widespread reluctance to engage with methodological issues. This contributes to the diminishing relevance of large amounts of scholarship for policy-makers who tend to privilege studies based on narrowly defined and soundly elaborated empirical methods. Clear and concise methodological rigour, systematization and ethnographic reflexivity, thus, play an incredibly important role.